The ANALYSIS OF WILLINGNESS TO PAY (WTP) VISITORS TO THE DEVELOPMENT OF RAFTING TOURISM IN SERAYU WATERSHED - Sudrajad, Nobel; Waridin, Waridin; Aminata, Jaka; Susilowati, Indah; Susilowati, Indah (Jurnal Ekonomi Kuantitatif Terapan; 2021: Vol. 14, No. 2, Agustus 2021 (pp.243-431)DO - 10.24843/JEKT.2021.v14.i02.p02, 2021)
Serayu Rafting Tourism utilizes the potential of Serayu Watershed located in Banjarnegara Regency. Serayu Rafting Tourism has the opportunity to increase its potential to become one of the leading tourism in Banjarnegara Regency. This study aims to identify the socioeconomic characteristics of tourists of Serayu Rafting attractions, estimate willingness to pay to determine the maximum potential price that is still willing to be paid in the development of Serayu Rafting attractions and analyze the factors that influence the willingness of visitors to pay the value chosen. This research uses CVM method and logistic regression analysis, with primary data obtained from survey to 105 respondents through multistage sampling technique and secondary data obtained from documents coming from relevant agencies, agencies or institutions. The results stated that the economic potential value of Rafting Serayu tourism object is quite good, because of 105 respondents as many as 95 respondents (90.5%) among them are willing to pay more for the development of tourism pbyek with a scenario 1 of Rp 10,000 and scenario 2 of Rp 25,000. Variable regional origin and income level affect willingness to pay, while variable gender, age, marital status and level of education do not affect willingness to pay.